Studying the Real-Time Interpretation of Novel Noun and Verb Meanings in Young Children - de Carvalho, Alex; Babineau, Mireille; Trueswell, John C.; Waxman, Sandra R.; Christophe, Anne (Frontiers in Psychology, 2019)
Decades of research show that children rely on the linguistic context in which novel words occur to infer their meanings. However, because learning in these studies was assessed after children had heard numerous occurrences of a novel word in informative linguistic contexts, it is impossible to determine how much exposure would be needed for a child to learn from such information. This study investigated the speed with which French 20-month-olds and 3-to-4-year-olds exploit function words to determine the syntactic category of novel words and therefore infer their meanings. In a real-time preferential looking task, participants saw two videos side-by-side on a TV-screen: one showing a person performing a novel action, and the other a person passively holding a novel object. At the same time, participants heard only three occurrences of a novel word preceded either by a determiner (e.g., “Regarde! Une dase! - “Look! A dase!”) or a pronoun (e.g., “Regarde! Elle dase!” - “Look! She’s dasing!”). 3-to-4-year-olds exploited function words to categorize novel words and infer their meanings: they looked more to the novel action in the verb condition, while participants in the noun condition looked more to the novel object. 20-month-olds, however, did not show this difference. We discuss possible reasons for why 20-month-olds may have found it difficult to infer novel word meanings in our task. Given that 20-month-olds can use function words to learn word meanings in experiments providing many repetitions, we suspect that more repetitions might be needed to observe positive effects of learning in this age range in our task. Our study establishes nevertheless that before age 4, young children become able to exploit function words to infer the meanings of unknown words as soon as they occur. This ability to interpret speech in real-time and build interpretations about novel word meanings might be extremely useful for young children to map words to their possible referents and to boost their acquisition of word meanings.